Clinical investigation of prostate carcinoma in the Third Teaching Hospital of Norman Bethune University of Medical Sciences - Xiao, L S (Hinyokika kiyo. Acta urologica Japonica, 1988)
Clinical and statistical investigations were performed on 157 patients with prostate carcinoma in the Third Teaching Hospital, Normal Bethune University experienced between January, 1950 and June, 1986. The number of patients with prostate carcinoma among other hospitalized patients showed a recent gradual increase. The patient's age at the time the disease was first diagnosed was most frequently between 60 and 69 years old with an average age of 63.3 years. Dysuria was the most prominent symptom, followed by frequency, retention and macroscopic hematuria. Duration between initial symptom and diagnosis was one to two years in most patients. The prostatic abnormality could be detected by rectal examination in all patients. Elevation of serum acid phosphatase was found in 24.4%. Such elevation was evident in 52.2% of the patients with metastatic lesions, compared to 14.4% of those without metastasis. Fourteen patients had metastasis to bone (8.9%), 13 to lymph nodes, 2 to lung and one to liver. According to the staging diagnosis, 19 patients (12.1%) had stage A, 78 patients (49.7%) had stage B, 20 patients (12.7%) had stage C and 40 patients (25.5%) had stage D carcinoma. Histological findings in 57 patients indicated adenocarcinomas; 39 cases (68.4%) were poorly differentiated, 12 cases (21.2%) were moderately differentiated and 6 cases (10.5%) were well differentiated. Modality of treatment was total prostatectomy in 2 cases (1.3%), antiandrogen therapy (orchiectomy and/or Stilbestrol) in 122 cases (77.7%), subcapsular prostatectomy in 7 cases (4.5%), symptomatic treatment in 5 cases and no treatment in 23 cases (14.6%)